Made to order : the designing of animals - Derry, Margaret E. (Margaret Elsinor), 1945- (University of Toronto Press, 2022)
"Animal breeding has been complicated by persisting factors across species, cultures, geography, and time. In Made to Order, Margaret E. Derry explains these factors and other breeding concerns in relation to both animals and society in North America and Europe over the past three centuries. Made to Order addresses how breeding methodology evolved, what characterized the aims of breeding, and the way structures were put in place to regulate the occupation. Illustrated by case studies on important farm animals and companion species, the book presents a synthetic overview of livestock breeding as a whole. It gives considerable emphasis to genetics and animal breeding in the post-1960 period, the relationship between environmental and improvement breeding, and regulation of breeding as seen through pedigrees. In doing so, Made to Order shows how studying the ancient human practice of animal breeding can illuminate the ways in which human thinking, theorizing, and evolving characterize our interactions with all-natural processes."--